Review on experimental study of Nd:YAG laser beam welding, with a focus on aluminium metal matrix composites - Banerjee, Amit Jyoti; Biswal, Manoja Kumar; Lohar, A K; Chattopadhyay, H; Hanumaiah, Naga (International Journal of Engineering and Technology, 2016)
The demand for high performance materials particularly in aviation and automobile industries gradually increases, CO2 and Nd: YAG lasers are becoming most popular in processing these advanced materials. In this context, one of the most important process is joining by welding. It has been a constant endeavour by researchers to explore various methods and techniques to enhance the process efficiency of autogenous Nd: YAG laser welding of various materials i.e. without any filler materials. In this work, we present a comprehensive review of major research findings for the last decades or so, obtained by researchers about the effect of process parameters on autogenous laser beam welding (LBW) process performance. Main objective of such experimental research was to improve laser weld quality such as tensile strength, weld micro structure, heat affected zone (HAZ), weld penetration etc. In this paper, discussions are also made about different parameter optimisation techniques, design of experiments (DOE), modelling and simulation techniques, adopted by different researchers to achieve optimum weld quality. This review tries to bring out a foresight for direction of further research needed in this field.
Keywords: Nd; YAG Laser Welding; Al-MMC; Weld Quality; DOE; Optimization.